Food Contamination by Microbes: Microbial Identification and Growth Factors - Andriyanto, Arif (Universitas Ibn Khaldun Bogor, 2025)
Food contamination by microbes is a serious issue that threatens public health and the sustainability of the food industry. This study aims to identify microbes that commonly contaminate food and analyze the factors influencing microbial growth in food materials. The methods used include a literature review of relevant scientific studies and data analysis from various sources. Findings indicate that bacteria such as Salmonella and viruses like Norovirus are often the primary causes of food poisoning, while factors such as temperature, humidity, and pH play a crucial role in microbial growth. In conclusion, a deep understanding of microbes and the environmental factors affecting their growth is essential for developing effective control strategies to reduce the risk of food contamination by microbes.